Determining best practices for integrating marketing and sales in organizations: using the Delphi technique - Watson, Kristin R., author; Gloeckner, Gene, advisor; Folkestad, James, committee member; Ingram, Thomas, committee member; Makela, Carole, committee member (Colorado State University. Libraries, 2017)
Using the Delphi technique; combining a thorough review of literature, with opinions of experts during three rounds of data collection, this study determined best practices for integrating marketing and sales in organizations. A purposeful, heterogeneous sample of marketing and sales executives, with a minimum of 30 years experience, in seven different industries, with 40 different organizations around the world participated as experts. Organizations that integrate marketing and sales can improve business performance; increase efficiency, effectiveness, customer and employee satisfaction. Eleven best practices for integrating marketing and sales in organizations were determined: communication; clearly defined roles, responsibilities and expectations; performance metrics; a customer focus; strategic planning; organizational knowledge; training and education; shared/aligned rewards; organizational intelligence (i.e. market, competitor, and customer information); lead management; and common technology platforms; resulting in the development of Watson's Integrated Marketing and Sales Best Practices (WIMS BP) model.
Keywords: Delphi; marketing; sales; integration; best practices; mixed methods